Cobalt catalyst and preparation method and application thereof
By designing the cobalt catalyst with Co-Co3O4(S)@NC-X structure, the existing cobalt catalyst has been solved, and the reaction of highly efficient oxidized alcohol derivatives under air atmosphere is achieved, with high efficiency, greenness and stability.
Patent Information
- Application Number
- CN202411815752.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-04
AI Technical Summary
The existing cobalt catalysts have problems of harsh reaction conditions, difficult separation and recycling, and need to be carried out under pure or oxygen-rich conditions. In traditional methods, excessive toxic oxidants are used to generate large amounts of chemical waste.
A cobalt catalyst with a structure of Co-Co3O4(S)@NC-X was designed, and prepared by polymerization and pyrolysis of glyoxal, dicyandiamide and cobalt nitrate hexahydrate, forming a spherical catalyst with cobalt core, tricobalt tetroxide and nitrogen-doped carbon shell from the inside to the outside, which can undergo oxidative esterification and dehydrogenation of alcohol derivatives under an air atmosphere.
This catalyst can efficiently oxidize alcohol derivatives as ester derivatives or dehydrogenated in water to carboxylic acid derivatives under an air atmosphere. The reaction process is efficient and green, and the catalyst has high stability and wide applicability.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to fine chemicals and preparation methods and applications thereof, and more specifically to a cobalt catalyst and preparation methods and applications thereof. Background Art
[0002] Cobalt catalysts have many uses, such as in the oxidative dehydrogenation of alcohols to produce carbonyl compounds. For example, Beller et al. synthesized a heterogeneous Co3O4-N@C catalyst (J. Am. Chem. Soc, 2013, 135, 10776-10782) and Li et al. prepared a Co@NC catalyst for the oxidation of alcohols to esters at 1 bar O2 (J. Am. Chem. Soc, 2017, 139, 811-818). Emilio Pardo's group prepared a MOF-supported Pd single-atom catalyst to oxidize benzyl alcohol to benzoic acid at 150°C and 4 atm O2 (J. Am. Chem. Soc, 2021, 143, 2581-2592). However, existing cobalt catalysts have problems such as harsh reaction conditions, difficulty in separation and recovery, and their reactions need to be carried out under pure oxygen or oxygen-rich conditions. Metal nanoparticles (MNPs) are widely used in the field of heterogeneous catalysis due to their high surface-to-volume ratio, abundant surface active sites and adjustable electronic structure. However, due to their high surface energy, MNPs are prone to migration and agglomeration during the catalytic process, resulting in decreased catalytic performance. Therefore, encapsulating MNPs into a carrier is an effective method to physically isolate MNPs and prevent them from migrating and agglomerating. In the prior art, various methods such as impregnation, electrostatic adsorption and uniform deposition-precipitation are used to control the particle size of MNPs to obtain better catalytic effects.
[0003] Carbonyl compounds (especially esters and carboxylic acids) are high value-added fine chemicals that are widely used in the chemical industry. The selective oxidation of cheap and readily available alcohols to carbonyl compounds is one of the most important and challenging tasks in organic synthesis, reflecting a green, economical and sustainable transformation process. In traditional methods, excessive amounts of toxic inorganic and organic oxidants are required to achieve the oxidative conversion of alcohols, which will generate a large amount of chemical waste.
[0004] The development of low-cost, excellent catalytic performance, and sustainable application of multiphase catalysts, especially for the oxidative esterification of alcohol derivatives to prepare ester derivatives in air, or the dehydrogenation of alcohol derivatives in water to prepare carboxylic acid derivatives in air, remains an important issue to be solved. Summary of the invention
[0005] The object of the present invention is to provide a cobalt catalyst which can overcome the deficiencies of the prior art, and to provide the preparation of the cobalt catalyst. Another object of the present invention is to use the cobalt catalyst of the present invention to carry out oxidative esterification of alcohol derivatives to prepare ester derivatives, and to use the catalyst of the present invention to carry out dehydrogenation of alcohol derivatives in water to prepare carboxylic acid derivatives.
[0006] The cobalt catalyst of the present invention has a structural formula of Co-Co3O4(S)@NC-X, wherein S is the particle size of the cobalt active site, and X is the pyrolysis temperature during catalyst preparation. Its microscopic structure is spherical in shape, with a cobalt core, cobalt oxide and a nitrogen-doped carbon shell from the inside to the outside. The spherical here refers to a shape similar to a sphere.
[0007] Preferably, the catalyst described in the present invention is any one of Co-Co3O4(49.4 nm)@NC-800, Co-Co3O4(12.2 nm)@NC-800, Co-Co3O4(5.4 nm)@NC-800 and Co-Co3O4(6.8 nm)@NC-800.
[0008] The preparation method of the cobalt catalyst Co-Co3O4(S)@NC-X of the present invention is as follows: firstly, glyoxal, dicyandiamide and cobalt nitrate hexahydrate are dissolved in deionized water, and then the solution is transferred to a stainless steel high-pressure reactor of polytetrafluoroethylene, and then heated to 120°C and then statically reacted, after the reaction is complete, filtered and dried to obtain a dark brown powder, and the dark brown powder is pyrolyzed in an argon atmosphere at 700°C to 900°C to obtain the product Co-Co3O4(S)@NC-X.
[0009] Preferably, in the preparation method of the cobalt catalyst Co-Co3O4(S)@NC-X of the present invention, 25 to 35 mmol of glyoxal, 50 to 70 mmol of dicyandiamide, and 0.53 mmol to 4.24 mmol of cobalt nitrate hexahydrate dissolved in water are used.
[0010] The catalyst of the present invention is prepared by using glyoxal and dicyandiamide as precursors, polymerizing in a hydrothermal process and coordinating with a hexahydrated cobalt nitrate metal precursor, and then pyrolyzing the polymer at high temperature in an inert atmosphere to convert it into a porous nitrogen-doped carbon shell, while encapsulating Co-Co3O4 nanoparticles in situ in the shell. Figure 1 .
[0011] The catalyst of the present invention can be used in the reaction of oxidative esterification of alcohol derivatives to ester derivatives in an air atmosphere, and can also be used in the reaction of dehydrogenating alcohol derivatives in water to prepare carboxylic acid derivatives in an air atmosphere.
[0012] The method for preparing ester derivatives by oxidative esterification of alcohol derivatives of the present invention comprises: adding a catalyst Co-Co3O4(S)@NC-X, benzyl alcohol or O-heterocyclic alcohol or aliphatic alcohol, potassium carbonate and aliphatic alcohol solvent into a reaction container, and reacting them completely and fully at 50°C to 70°C in an air atmosphere, wherein the alcohol derivative in the reaction refers to any one of benzyl alcohol, 2-fluorobenzyl alcohol, 4-fluorobenzyl alcohol, 2-chlorobenzyl alcohol, 4-chlorobenzyl alcohol, 2-bromobenzyl alcohol, 4-bromobenzyl alcohol, 4-methylbenzyl alcohol, 2-methylbenzyl alcohol, 4-methoxybenzyl alcohol, 4-nitrobenzyl alcohol, cinnamyl alcohol, terephthalylinol, furanyl alcohol, 2,5-furanyl alcohol, 2-aminobenzyl alcohol, 1-butanol, 1-pentanol, n-hexanol, 1-octanol, decanol or 1-dodecanol; and the aliphatic alcohol solvent is any one of methanol, ethanol, propanol or butanol.
[0013] The method for preparing carboxylic acid derivatives by dehydrogenating alcohol derivatives in water is as follows: adding a catalyst Co-Co3O4(S)@NC-X, an alcohol derivative, potassium hydroxide and deionized water into a reaction container, and carrying out a sufficient reaction at 60°C to 100°C in an air atmosphere; The alcohol derivative refers to any one of benzyl alcohol, 2-fluorobenzyl alcohol, 4-fluorobenzyl alcohol, 2-chlorobenzyl alcohol, 4-chlorobenzyl alcohol, 2-bromobenzyl alcohol, 4-bromobenzyl alcohol, 4-methylbenzyl alcohol, 2-methylbenzyl alcohol, 4-methoxybenzyl alcohol, 4-nitrobenzyl alcohol, cinnamyl alcohol, terephthalylidene alcohol, furanyl alcohol, 2,5-furandimethanol, 2-aminobenzyl alcohol, 1-butanol, 1-pentanol, n-hexanol, 1-octanol, decanol or 1-dodecanol; the solvent is water; and the amount of potassium hydroxide added is 0.5 to 2.0 times the molar amount of cobalt in the active site.
[0014] See Formula 1 for the above reaction.
[0015]
[0016] Formula 1 More preferably, the catalyst used in the method for preparing ester derivatives by oxidative esterification of alcohol derivatives or the method for preparing carboxylic acid derivatives by dehydrogenation of alcohol derivatives in water of the present invention is any one of Co-Co3O4(49.4 nm)@NC-800, Co-Co3O4(12.2 nm)@NC-800, Co-Co3O4(5.4 nm)@NC-800 and Co-Co3O4(6.8 nm)@NC-800 or a combination of any two of them.
[0017] The experiment of the present invention shows that in the process of preparing the catalyst, different amounts of the metal precursor hexahydrate cobalt nitrate are added, and after polymerization and coordination processes, pyrolysis is performed at different high temperatures in a nitrogen atmosphere, and the particle sizes of the obtained cobalt active sites are different. In the process of preparing the catalyst of the present invention, a polymer precursor of cobalt is first generated by polymerization of glyoxal, dicyandiamide and cobalt nitrate, and then pyrolysis is performed to finally obtain a spherical catalyst having a cobalt core-cobalt tetroxide-nitrogen-doped carbon layer structure from the inside to the outside.
[0018] When performing oxidative esterification of alcohol derivatives or dehydrogenation of alcohol derivatives in water to prepare carboxylic acid derivatives, molecular oxygen as an oxygen source has attracted great attention due to its environmental friendliness and zero pollution. Before the disclosure of the present invention, there were few reports on the selective oxidation of alcohol derivatives using oxygen (especially air), while the catalyst of the present invention can achieve the selective oxidation of alcohol derivatives in an air atmosphere.
[0019] The present invention has the following advantages: 1. The present invention utilizes cheap precursors to design and prepare catalysts, and the cobalt active sites are confined in the nitrogen-doped carbon shell, which effectively prevents the aggregation and loss of the cobalt active sites and improves the stability of the catalyst.
[0020] 2. In the preparation of the catalyst of the present invention, the particle size of the active site cobalt in the final catalyst can be regulated by adding different amounts of cobalt metal precursors or by controlled pyrolysis at different temperatures, thereby regulating the activity and selectivity of the catalyst to meet different needs.
[0021] 3. Using alcohol derivatives as substrates and air as an oxygen source, the selective catalytic oxidation synthesis of carbonyl compounds has a high product yield and the reaction process is efficient and green. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the catalyst preparation method of the present invention.
[0023] Figure 2 Transmission electron microscope images of catalysts with different metal particle sizes of the present invention, including: (a) Co-Co3O4(49.4)@NC-800, (b) Co-Co3O4(12.2)@NC-800, (c) Co-Co3O4(5.4)@NC-800, (d) Co-Co3O4(6.8)@NC-800, (e) TEM image of Co-NC-800 catalyst; (f) HRTEM image, (g) dark field TEM image and (h) overlapping element distribution map of Co-Co3O4(5.4)@NC-800 catalyst.
[0024] Figure 3These are scanning electron microscope images of the catalysts of the present invention at different pyrolysis temperatures, including: (a) TEM images of Co-Co3O4@NC-700, (b) Co-Co3O4(40.7)@NC-900; (cd) SEM images of Co-Co3O4@NC-700, (e) Co-Co3O4(5.4)@NC-800 and (f) Co-Co3O4(40.7)@NC-900.
[0025] Figure 4 The X-ray powder diffraction spectra of the catalysts of different particle sizes and different pyrolysis temperatures of the present invention, wherein: (a) catalysts of different particle sizes; (b) catalysts of different pyrolysis temperatures.
[0026] Figure 5 X-ray photoelectron spectra of the catalysts of the present invention at different pyrolysis temperatures, including: (a) high-resolution C1s fine spectrum; (b) high-resolution N1s fine spectrum; (c) high-resolution Co2p fine spectrum.
[0027] Figure 6 The repeated reaction diagrams of the catalyst of the present invention include: (a) a cyclic reaction diagram of the oxidation esterification of benzyl alcohol; (b) a cyclic reaction diagram of the dehydrogenation of benzyl alcohol in water to produce benzoic acid. DETAILED DESCRIPTION
[0028] The following are examples of the present invention and comparative examples.
[0029] 1. Catalyst Preparation Example Glyoxal (29.74 mmol), dicyandiamide (59.47 mmol) and different amounts of cobalt nitrate hexahydrate (4.24 mmol, 2.12 mmol, 1.06 mmol, 0.53 mmol) were dissolved in deionized water (30 mL), and the solution was transferred to a stainless steel autoclave with polytetrafluoroethylene, heated to 120 °C and left to stand for 24 h. After the reaction was completed, the dark brown powder was filtered and dried, and then pyrolyzed at 800 °C for 2 h under argon atmosphere (see the catalyst preparation process). Figure 1 ). The amount of cobalt nitrate hexahydrate added during the preparation process was different, thereby regulating the particle size of the active site Co nanoparticles in the catalyst, and correspondingly obtaining Co-Co3O4(49.4)@NC-800, Co-Co3O4(12.2)@NC-800, Co-Co3O4(5.4)@NC-800 and Co-Co3O4(6.8)@NC-800 catalysts.
[0030] Glyoxal (29.74 mmol), dicyandiamide (59.47 mmol) and cobalt nitrate hexahydrate (1.06 mmol) were dissolved in deionized water (30 mL), and the solution was transferred to a stainless steel autoclave with polytetrafluoroethylene, heated to 120 °C and left to stand for 24 h. After the reaction was completed, the dark brown powder was filtered and dried, which was pyrolyzed at 700 °C and 900 °C under argon atmosphere for 2 h to obtain Co-Co3O4@NC-700 and Co-Co3O4(40.7)@NC-900 catalysts.
[0031] In the catalyst preparation process, the feed amounts of glyoxal and dicyandiamide remain unchanged, the hexahydrated cobalt nitrate precursor is not added, and the other preparation conditions are the same to obtain the NC-800 catalyst; 1,10-phenanthroline monohydrate (309 mg, 1.56 mmol) and hexahydrated cobalt nitrate (1.06 mmol) are added to the reaction system, and the other preparation conditions are the same to obtain the Co-NC-800 catalyst; g -C3N4 was used as the carrier, cobalt nitrate hexahydrate (1.06 mmol) was used as the metal precursor, glyoxal and dicyandiamide were not added, and the other preparation conditions were the same to obtain Co / g -C3N4-800 catalyst.
[0032] Characterization of catalysts: The contents of Co and N in different control catalysts can be determined by ICP and EA as shown in Table 1. In order to explore the microscopic morphology of the catalyst, the catalyst was characterized by transmission electron microscopy and scanning electron microscopy. Figure 2 It shows that as the Co content decreases from 22.9%, 18.1% to 11.5%, the average particle size of Co nanoparticles decreases from 49.4 nm, 12.2 nm to 5.4 nm. However, when the Co content is further reduced to 7.1%, a nitrogen-doped carbon nanotube-encapsulated Co species catalyst is produced, and the average particle size of the Co species is 6.8 nm, indicating that more N atoms are beneficial to stabilizing metal ions and adjusting the particle size ( Figure 2 ad). When 1,10-phenanthroline is introduced into the preparation process, a single-atom Co-NC-800 catalyst ( Figure 2 e), no CoNPs were observed. The HRTEM image shows different lattice fringes with lattice spacings of 0.34 nm, 0.23 nm, and 0.20 nm, which are attributed to the (002) crystal plane of graphitic carbon, the (311) crystal plane of Co3O4, and the (111) crystal plane of Co, respectively. Figure 2f). Overlapping EDS element distribution diagram (2h) shows that O element is mainly distributed around Co element, indicating that a structure with Co as the core, Co3O4 layer in the middle, and nitrogen-doped carbon layer as the outer layer is formed. N element is evenly distributed around C element, indicating that N atoms are successfully doped into carbon material, and Co-Co3O4NPs are encapsulated in the nitrogen-doped carbon layer. Finally, a spherical catalyst with a microstructure of cobalt core, cobalt oxide, and nitrogen-doped carbon shell from inside to outside is obtained.
[0033]
[0034] Since the Co-Co3O4(5.4)@NC-800 catalyst has the smallest particle size and the highest dispersibility, the effect of different pyrolysis temperatures on particle size was studied based on this catalyst. Figure 3 As shown in the figure, the catalysts pyrolyzed at 700℃ and 900℃ still retain the irregular spherical morphology of the polymer precursor. No Co NPs were observed from the TEM image of the Co-Co3O4@NC-700 catalyst, and a large number of carbon nanotubes were observed to be formed on the catalyst surface from the SEM image. The N contents of Co-Co3O4(5.4)@NC-800 and Co-Co3O4(40.7)@NC-900 catalysts were 6.9% and 1.8%, respectively, while the N content of Co-Co3O4@NC-700 catalyst was as high as 31.1%, indicating that the graphitization and carbonization of the polymer precursor at 700℃ were incomplete. Studies have shown that N atoms can anchor and stabilize metals through metal-heteroatom interactions. The low N content of the Co-Co3O4(40.7)@NC-900 catalyst resulted in the agglomeration of CoNPs, with an average particle size of 40.7 nm.
[0035] The above results are consistent with the XRD results ( Figure 4 ), the characteristic peak at 26° corresponds to the (002) crystal plane of graphite carbon. At the same time, the three diffraction peaks at 2θ = 44.2°, 51.5° and 75.7° correspond to Co 0 (JCPDS No. 15-806) (111), (200) and (220) crystal planes. Due to the low content of Co3O4, its diffraction peak is weak. The diffraction peak intensities of different catalysts are as follows: Co-Co3O4(49.4)@NC-800>Co-Co3O4(12.2)@NC-800>Co-Co3O4(5.4)@NC-800>Co-Co3O4(6.8)@NC-800>Co-NC-800, which is consistent with the gradually decreasing Co content ( Figure 4 a). The diffraction peak intensity of graphite carbon in Co-Co3O4@NC-700 catalyst is weak, and no Co 0Compared with the Co-Co3O4(5.4)@NC-800 catalyst, the Co-Co3O4(40.7)@NC-900 catalyst has a more obvious Co NPs and a higher Co content. 0 Characteristic peaks and worse dispersion ( Figure 4 b).
[0036] XPS spectroscopy can analyze the composition and valence of catalyst elements. C, N, O, and Co exist in the catalyst ( Figure 5 ). The high-resolution C1s fine spectrum shows typical CC (284.6 eV), CN (285.5 eV), CO (286.7 eV) and OC=O (288.5 eV) peaks ( Figure 5 a). High-resolution N1s fine spectrum ( Figure 5 The three peaks in b) are attributed to pyridinic N (398.3 eV), pyrrolic N (399.5 eV) and graphitic N (401.1 eV). Studies have shown that graphitic N can promote electron transfer. The high-resolution Co2p fine spectrum can be divided into Co2p 3 / 2 Co 0 (779.9 eV), Co 3+ (781.0 eV), Co 2+ (782.4 eV) and Co2p 1 / 2 Co 0 (794.2 eV), Co 3+ (795.2 eV), Co 2+ (796.7 eV). 784.6 eV and 802.8 eV are satellite peaks ( Figure 5 c) With the increase of pyrolysis temperature, Co 0 The proportion of Co 2+ and Co 3+ The ratio of x Species decline and Co 0 These results indicate that the mixed Co 0 and Co3O4 phases exist in the catalyst.
[0037] 2. Preparation Example of Carbonyl Derivatives (Evaluation of Catalyst Performance) The present invention has conducted relevant exploration on the application of the catalyst. Table 2 shows the results of the oxidative esterification reaction of benzyl alcohol catalyzed by catalysts of different particle sizes, catalysts of different pyrolysis temperatures and control catalysts in an air atmosphere. First, for catalysts of different particle sizes, the atomically dispersed Co-NC-800 catalyst has the lowest activity and selectivity. When Co NPs are formed, the activity and selectivity of the catalyst are greatly improved. As the particle size of Co NPs decreases from 49.4 nm and 12.2 nm to 5.4 nm, the conversion rate of benzyl alcohol increases from 76.5% and 82.9% to 99.9%. The Co-Co3O4(6.8)@NC-800 catalyst exhibits lower activity and selectivity due to larger Co NPs and lower Co content. Secondly, for catalysts of different pyrolysis temperatures, the Co-Co3O4@NC-700 catalyst exhibits a conversion rate of 7.9% and a selectivity of 76.1%, which is due to the main formation of Co3O4 species in the catalyst. Due to the larger Co NPs, the Co-Co3O4(40.7)@NC-900 catalyst has a relatively low conversion of 80.6% and selectivity of 96.6%. Finally, the control catalyst Co / NC-800 (without glyoxal) has a conversion of only 13.2%, which is due to the reaction of dicyandiamide with Co. 2+ The coordination effect is weak and no Co species are formed in the catalyst. Due to the formation of larger Co NPs and nanotubes, the Co / g -C3N4-800 catalyst showed low conversion and selectivity. These results indicate that the structure of the polymer plays a crucial role in stabilizing Co-Co3O4NPs, improving the dispersion of active sites and controlling the metal particle size. The reaction basically did not occur when NC-800 was used as a catalyst or without a catalyst, indicating that Co species catalyze the reaction as the main active site. In summary, the Co-Co3O4(5.4)@NC-800 catalyst showed the highest activity and selectivity.
[0038]
[0039] At the same time, the inventors unexpectedly discovered that the optimal catalyst also exhibited excellent performance in the dehydrogenation of benzyl alcohol to produce benzoic acid. The reaction was carried out in an air atmosphere with H2O as solvent, see Table 3. First, different equivalents of KOH were screened. When KOH was not added, the reaction had only a conversion rate of 15.4% and a selectivity of 15.2%, indicating that KOH is indispensable in the reaction. The reaction showed high activity at 1.0 and 2.0 equivalents of KOH. From an economic point of view, 1.0 equivalent of KOH was used for subsequent reactions. The reaction activity decreased with decreasing reaction temperature (80°C and 60°C). The reaction was also difficult to carry out without a catalyst or in the presence of an NC-800 catalyst. At the same time, the Co-Co3O4(5.40)@NC-800 catalyst showed excellent reusability and catalyst stability after ten cycles of oxidative esterification and oxidative dehydrogenation of benzyl alcohol to produce benzoic acid, see. Figure 6 .
[0040]
[0041] The general applicability of the catalyst was first investigated by catalyzing the esterification of various substituted benzyl alcohols, O-heterocyclic alcohols and fatty alcohols, see Table 4. Para-halogenated benzyl alcohols were oxidized to the corresponding esters with >99% conversion and selectivity. Due to steric hindrance, ortho-halogenated benzyl alcohols had relatively low conversion (>70%) and selectivity (>90%) (2a-7a). Ortho- and para-methyl-substituted benzyl alcohols showed moderate conversion (>70%) and selectivity (>60%) (8a-9a). 4-Methoxybenzyl alcohol showed high conversion (>99%) and selectivity (>99%) (10a). 4-Nitrobenzyl alcohol was converted with >99% conversion and 89.6% selectivity (11a). Cinnamyl alcohol and 1,4-benzenedimethanol can be converted into methyl cinnamate (conversion>99%, selectivity>99%) and dimethyl terephthalate (conversion>99%, selectivity88.0%) with high added value in industry (Nos. 12a-13a). Heterocyclic alcohols such as furfuryl alcohol and 5-hydroxymethylfurfural can be well converted into the corresponding esters (conversion>70%, selectivity>50%) (Nos. 14a-15a). In addition, fatty alcohols decanol and 1-dodecanol can be oxidized to the corresponding esters with moderate conversion (>40%) and high selectivity (>97%) (Nos. 16a-17a). Other fatty alcohols (such as ethanol, propanol and butanol) can also react with benzyl alcohol to form the corresponding alkyl esters (conversion>90%, selectivity>80%) (Nos. 18a-20a), further expanding the applicability of the catalyst.
[0042] The versatility of the catalyst of the present invention was further confirmed by the selective conversion of aromatic alcohols and aliphatic alcohols into corresponding acids, both of which were converted in high yields (Table 5, Nos. 1c-12c). Except for 4-nitrobenzyl alcohol with a strong electron-NO2 group, electronic factors and steric effects have little effect on the reaction (No. 13c). Aliphatic primary alcohols (1-butanol, 1-pentanol, n-hexanol, 1-octanol, 1-decanol and 1-dodecanol) can also be converted into corresponding acids with a conversion rate of 30%-99% and a selectivity of more than 98% (Nos. 14c-19c). These results all indicate that the Co-Co3O4(5.4)@NC-800 catalyst with air as oxygen source has excellent catalytic performance and wide applicability. In addition, most of the catalytic systems reported for similar reactions are based on precious metal catalysts and use pure O2 as an oxygen source, so the present invention is more economical (using earth-abundant transition metals), efficient (excellent catalytic activity) and green (air as an oxygen source).
[0043] The present invention discloses a cobalt catalyst and a preparation method and application thereof. The cobalt catalyst of the present invention has the structural formula Co-Co3O4(S)@NC-X, wherein: S is the particle size of the cobalt active site, X is the pyrolysis temperature during the preparation of the catalyst, and its microscopic structure is a spherical shape consisting of a cobalt core, cobalt oxide and a nitrogen-doped carbon shell from the inside to the outside. The present invention utilizes a cheap precursor design to prepare the catalyst, and the cobalt active site is confined in the nitrogen-doped carbon shell, which effectively prevents the agglomeration and loss of the cobalt active site and improves the stability of the catalyst. The cobalt catalyst of the present invention can be used to selectively catalyze and oxidize the product of synthesizing carbonyl compounds using alcohol derivatives as substrates and air as an oxygen source, and has the advantages of high yield, efficient reaction process and greenness.
[0044] Table 4 Cross-esterification of aromatic alcohols and fatty alcohols catalyzed by Co-Co3O4(5.4)@NC-800
[0045] Table 5 Co-Co3O4(5.4)@NC-800 catalyzes the oxidation of aromatic alcohols and fatty alcohols to the corresponding acids .
Claims
1. A cobalt catalyst, characterized in that Its structural formula is Co-Co3O4(S)@NC-X, and its microscopic structure is a spherical shape consisting of a cobalt core, cobalt oxide and a nitrogen-doped carbon shell from the inside to the outside. In the structural formula: S is the particle size of the cobalt active site, and X is the pyrolysis temperature during catalyst preparation.
2. The catalyst according to claim 1, characterized in that The catalyst is any one of Co-Co3O4(49.4 nm)@NC-800, Co-Co3O4(12.2 nm)@NC-800, Co-Co3O4(5.4 nm)@NC-800 and Co-Co3O4(6.8 nm)@NC-800.
3. The preparation method of the cobalt catalyst Co-Co3O4(S)@NC-X according to claim 1, characterized in that First, glyoxal, dicyandiamide and cobalt nitrate hexahydrate were dissolved in deionized water, and then the solution was transferred to a stainless steel high-pressure reactor with polytetrafluoroethylene, heated to 120°C and allowed to react quiescently. After the reaction was complete, it was filtered and dried to obtain a dark brown powder. The dark brown powder was pyrolyzed at 700°C to 900°C in an argon atmosphere to obtain the product Co-Co3O4(S)@NC-X.
4. The method for preparing the cobalt catalyst Co-Co3O4(S)@NC-X according to claim 3, characterized in that The amount of glyoxal dissolved in water is 25 to 35 mmol, the amount of dicyandiamide is 50 to 70 mmol, and the amount of cobalt nitrate hexahydrate dissolved in water is 0.53 mmol to 4.24 mmol.
5. Use of the catalyst according to claim 1 or 2 in the reaction of oxidative esterification of alcohol derivatives to produce ester derivatives in air atmosphere or dehydrogenation of alcohol derivatives in water to produce carboxylic acid derivatives.
6. Use of the catalyst according to claim 5 in the reaction of oxidative esterification of alcohol derivatives into ester derivatives under air atmosphere, characterized in that: Add the catalyst Co-Co3O4(S)@NC-X, benzyl alcohol or O-heterocyclic alcohol or fatty alcohol, potassium carbonate and fatty alcohol solvent into a reaction vessel and allow the reaction to fully proceed at 50°C to 70°C in an air atmosphere; The alcohol derivatives are any one of benzyl alcohol, 2-fluorobenzyl alcohol, 4-fluorobenzyl alcohol, 2-chlorobenzyl alcohol, 4-chlorobenzyl alcohol, 2-bromobenzyl alcohol, 4-bromobenzyl alcohol, 4-methylbenzyl alcohol, 2-methylbenzyl alcohol, 4-methoxybenzyl alcohol, 4-nitrobenzyl alcohol, cinnamyl alcohol, terephthalylidene alcohol, furanyl alcohol, 2,5-furanyl alcohol, 2-aminobenzyl alcohol, 1-butanol, 1-pentanol, n-hexanol, 1-octanol, decanol or 1-dodecanol; the fatty alcohol solvent is any one of methanol, ethanol, propanol or butanol.
7. Use of the catalyst according to claim 5 in the reaction of dehydrogenating alcohol derivatives in water to prepare carboxylic acid derivatives under air atmosphere, characterized in that: The catalyst Co-Co3O4(S)@NC-X, alcohol derivatives, potassium hydroxide and deionized water are added into a reaction vessel and reacted fully at 60-100°C in an air atmosphere; The alcohol derivative refers to any one of benzyl alcohol, 2-fluorobenzyl alcohol, 4-fluorobenzyl alcohol, 2-chlorobenzyl alcohol, 4-chlorobenzyl alcohol, 2-bromobenzyl alcohol, 4-bromobenzyl alcohol, 4-methylbenzyl alcohol, 2-methylbenzyl alcohol, 4-methoxybenzyl alcohol, 4-nitrobenzyl alcohol, cinnamyl alcohol, terephthalylidene alcohol, furanyl alcohol, 2,5-furandimethanol, 2-aminobenzyl alcohol, 1-butanol, 1-pentanol, n-hexanol, 1-octanol, decanol or 1-dodecanol; the solvent is water; and the amount of potassium hydroxide added is 0.5 to 2.0 times the molar amount of cobalt in the active site.
8. The method according to claim 6 or 7, characterized in that The catalyst used is any one of Co-Co3O4(49.4 nm)@NC-800, Co-Co3O4(12.2 nm)@NC-800, Co-Co3O4(5.4 nm)@NC-800 and Co-Co3O4(6.8 nm)@NC-800 or a combination of any of them.